CREATING A MASCOT WITH COMMUNITY INVOLVEMENT TO PROMOTE LOCAL IDENTITY OF BAN CHIEN SUBDISTRICT HAN KHA DISTRICT CHAINAT PROVINCE - Kangvaravoot, Chalit; Samutrak, Phairoj (Fine Arts Journal: Srinakharinwirot University, 2024)
The purposes of this research are 1) to analyze and synthesize the data on the community identity of Ban Chien Sub-district, Hunkha District, Chai Nat Province, and 2) to create mascots with community participation. The conceptual framework of the research emphasizes the design and creation of mascots with the involvement of the community to promote the local identity of Chainat Province which is considered as a collaboration between the community and researchers to search for the identity in the context of Ban Chien Sub-district. The research procedures included: 1) The data collection was proceeded by the qualitative method through focus group meetings and in-depth interviews to collect data for synthesizing the local identity; 2) The creative design of the mascots from local identity with community’s involvement was proceeded by assessing the suitability of the mascot sketch by Ban Chien sub-district communities and the improvements according to suggestions were developed into the mascot based on the local identities; 3) The evaluation of the mascot was proceeded by 30 guests and the communities in Ban Chien Sub-district, obtained by the purposive selection. The results showed that there were 2 types of the identity of Ban Chien Sub-district covering the tangible identity (e.g., Chien Mak clock tower) and intangible identity (e.g., The story of the origin of the name of Ban Chien Subdistrict). The results regarding the mascot creation with community involvement, namely Nong Chien Mak, used the creative processes of the pattern being synthesized from the name of Ban Chien Subdistrict, and inspired by the story. The creation applied creative principles to cut down the shape of Chien Mak and Chien Mak Clock Tower to express the identity of the community. In other words, Chien Mak represents a way of life, as well as the culture of eating betel nuts for the elderly that can still be seen and may disappear over time. The design used the two-part character principles and the simple format to make it easy to remember and become the representative media which includes the story content to bring the mascot to be alive and enter the memory of the viewers. Meanwhile, the assessment results from general people and locals in the community (n=30) indicated that Nong Chien Mak was created appropriately at the highest level (= 4.53, S.D. = 0.51).